Deaf-centric and Sovereign: Translation as a Tool for Changing Audism and English Dominance (Altre Modernità, 2019)
This essay explores the way two languages typically considered “less-common”can be connected through creative composition, translation and interpretation. Working together in a course on Great Lakes History at the University ofWisconsin-Milwaukee, three co-authors confront the problem of creating culturallyinformed translations of two indigenous texts. One author is the professor of thecourse and an Anishinaabe poet sharing her own work with students. One author is awriter and sign-language interpreter. One author is a long-distance Anishinaabecultural consultant. In the class, students learn to read and recite two texts originallycomposed in Anishinaabemowin and translated into English. With Deaf studentsenrolled in the course, an additional translation into American Sign Language (ASL) isneeded. An ASL interpretation of each text based only on the English translation isuseful, but does not contain the full meaning of the Anishinaabemowin original.Together the team created an ASL version which reflects more detail and culturalnuances. The primary aim of this essay is to demonstrate a method for reducingaudism by using inter-cultural methodologies to produce more accurate translationsand decolonial and deaf-centric interpretations. A secondary aim of the essay is tocompare and contrast Anishinaabemowin and ASL leading to the suggestion thatmore work should be done to directly connect indigenous and sign languages.